Pengaruh Indeks Dow Jones Industrial Average (DJIA), Tingkat Inflasi, Bi 7-Day Repo Rate, dan Kurs USD/IDR terhadap Indeks Saham Syariah Indonesia (ISSI) di Bursa Efek Indonesia (BEI) - Safiinatul Jannah Noviyani; Rusdi Hidayat Nugroho (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Indonesia is one of the largest Muslim countries in the world that makes sharia investments in the capital market with efforts to develop the Islamic financial sector. Several factors that influence stock price fluctuations include global indices and macroeconomic variables. This study aims to determine the simultaneous and partial effect of the Dow Jones Industrial Average (DJIA), Inflation Rate, BI 7-Day Repo Rate, and USD/IDR Exchange Rate on the Indonesian Sharia Stock Index (ISSI). This study uses secondary data in the form of monthly index summary reports obtained from financial websites. The object of research is the Indonesian Sharia Stock Index. This study has a population of 60 data with the determination of the sample using saturated samples. The data analysis technique used multiple linear regression analysis techniques. Hypothesis testing using the F test and T test. The results of the simultaneous test analysis (Test F) show that the variables of the Dow Jones Industrial Average (DJIA) (X1), Inflation Rate (X2), BI 7-Day Repo Rate (X3) and USD/IDR Exchange Rate (X4) has a significant influence on the Indonesian Sharia Stock Index (ISSI) on the Indonesia Stock Exchange (IDX) Period August 2016 – July 2021. Partially, the DJIA Index and the Inflation Rate have a positive and significant effect on Indonesian Sharia Stock Index. Meanwhile, the BI 7-Day Repo Rate and the USD/IDR Exchange Rate have a negative and significant effect on Indonesian Sharia Stock Index.